Efforts To Improve Math Learning Outcomes Through Problem Solving Learning Models - Trisnawati, Feni; Suminar, Tri; Andaryani, Eka Titi (UIN Sultan Aji Muhammad Idris Samarinda, 2025)
This study aims to improve the mathematics learning outcomes of fifth-grade students through the implementation of a problem-solving learning model that emphasizes the ability to understand, analyze, and solve problems independently or in groups. The method used is Classroom Action Research (CAR), conducted in two cycles with 32 students as subjects at an elementary school in Jakarta. Data were collected through learning outcome tests, observations, and interviews. The results showed an increase in the average student score from 58.50 before the intervention to 65.00 in the first cycle and 75.50 in the second cycle, along with an increase in the percentage of students meeting the Minimum Mastery Criteria (MMC) from 43.75% to 87.50%. Additionally, there was an improvement in students’ learning motivation, logical thinking skills, and collaboration. These findings indicate that the problem-solving learning model is effective in enhancing mathematics learning outcomes and is therefore recommended for continuous application by teachers in the learning process.